2009
DOI: 10.1002/marc.200900160
|View full text |Cite
|
Sign up to set email alerts
|

Poly(p‐phenylene ethynylene) Incorporating Sterically Enshrouding m‐Terphenyl Oxacyclophane Canopies

Abstract: A sterically encumbered m-terphenyl oxacyclophane substituted with two aryl iodide substituents has been prepared as a versatile monomer for the preparation of π-conjugated polymers. The monomer has been used to prepare a poly(p-phenylene ethynylene) derivative (P1) incorporating oxacyclophane units as canopies that shield one side of the π-system from inter-chain interactions. The photophysical properties of P1 in dilute solution compare well to those of a poly(p-phenylene ethynylene) derivative (P2) that lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…[39] This dual inter-p-system interaction/steric canopy module strategy was recently extended by fashioning a sterically encumbered m-terphenyl unit into an oxacyclophane for incorporation into PPE derivative 9 ( Figure 9). [42] Despite the significantly larger macrocyclic scaffold in 9 versus that in 8a, its inter-p-system distance is only slightly larger (3.41 Å in 9 versus 3.33 Å in 8a). This is likely due to the greater conformational mobility of the larger macrocycle, which also explains its ability to accommodate an interplanar angle of 288 (cf.…”
Section: Scaffolded Inter-p-system Interactions In Conjugated Polymersmentioning
confidence: 97%
“…[39] This dual inter-p-system interaction/steric canopy module strategy was recently extended by fashioning a sterically encumbered m-terphenyl unit into an oxacyclophane for incorporation into PPE derivative 9 ( Figure 9). [42] Despite the significantly larger macrocyclic scaffold in 9 versus that in 8a, its inter-p-system distance is only slightly larger (3.41 Å in 9 versus 3.33 Å in 8a). This is likely due to the greater conformational mobility of the larger macrocycle, which also explains its ability to accommodate an interplanar angle of 288 (cf.…”
Section: Scaffolded Inter-p-system Interactions In Conjugated Polymersmentioning
confidence: 97%
“…The m-terphenyl unit has been selected to provide the desired steric cleft. Such m-terphenyl units have found increasing utility as steric protecting groups [19][20][21] to shield chromophores from extraneous interp-system interactions in CPs (Figure 1A [22] and B [23] ) and in ligandmodified scaffolds for conducting metallopolymers ( Figure 1C) [24] as a means of providing steric coordination control against metal-induced cross-linking. [25] Results and Discussion…”
Section: Introductionmentioning
confidence: 99%
“…Polymers feature significantly longer π‐conjugated multi‐aryl segments than small molecules, thus the relative contribution of intermolecular π–π interactions to spectroscopic properties will be greater for polymers. Mixed methoxy/hexyloxy P1, prepared as a baseline CP for spectroscopic properties exhibited by a PPE when no steric constraints on interchain interactions are present, displayed λ max = 427 nm and λ em = 462 nm. Replacing the methyl substituents in P1 with the terphenyl canopy in P2 did not affect the absorption wavelength but produced a 10 nm bathochromic shift in fluorescence ( λ em = 472 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical studies have suggested that a face‐to‐face π‐stacking interaction with a plane‐to‐plane distance of 3.2–4.0 Å is ideal for facilitating charge mobility through a CP film . Some investigators have sought to alleviate the complication of inter‐π‐system interaction influences on polymer properties by appending the polymers with sterically encumbered substituents to prevent close contacts between polymer chains . Other researchers have devised molecular scaffolding and covalent crosslinking strategies to constrain adjacent polymer chains in near‐ideal orientations to improving charge/energy transport through a material .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation